Assessment of oxidative and shelf life stability of lycopene enriched butter during storage - Md. Nazmus Salehin; Sazzadul Islam Khan; Md Shahjahan Kabir; Konok Kumar; Sidratul Montaha; Md. Arefuzzaman; M. Burhan Uddin; Maruf Ahmed (Food Chemistry Advances)
In this study, butter samples were prepared at different concentrations of lycopene extract (S1: 0 mg/kg, S2: 200 mg/kg, S3: 400 mg/kg, S4: 600 mg/kg). Then, the lycopene content, physicochemical properties, color properties, microbiological stability, and retention of lycopene (%) in butter were studied over a 150-day storage period. Among the butter samples, S3 (400 mg/kg lycopene extract) exhibited significantly lower levels of free fatty acids (FFAs) and peroxide values (PVs) compared to the other samples. The lycopene content decreased for all samples (S2, S3, and S4) over the storage period. Lycopene enriched butter sample S3 (400 mg/kg lycopene extract) had the highest retention (41.26 %), while S4 (600 mg/kg lycopene extract) had the lowest retention (37.08 %) of lycopene content. Lactic acid bacteria were not hampered by the addition of lycopene extract. Lycopene enriched butter samples were well-accepted by the consumers. These findings suggest lycopene extract as an effective natural additive to enhance the oxidative stability and shelf life of butter.